Molecular beam epitaxial In2Te3 electronic devices - Imhwan Kim; Jinseok Ryu; Eunsu Lee; Sangmin Lee; Seokje Lee; Wonwoo Suh; Jamin Lee; Miyoung Kim; Hong seok Oh; Gyu-Chul Yi (NPG Asia Materials)
Abstract We report on the electrical characteristics of field-effect transistors (FETs) and Schottky diodes based on In2Te3 grown on hexagonal boron nitride (h-BN) substrates utilizing molecular beam epitaxy (MBE). A two-step growth method was used to increase surface coverage and large grain sizes for high-quality In2Te3. Scanning transmission electron microscopy (STEM) imaging revealed an atomically clean and abrupt interface between the In2Te3 and h-BN substrates. Compared with the previously reported In2Te3 FETs, the MBE-grown In2Te3 FETs exhibited superior electrical properties, including a mobility of 6.07 cm2 V−1 s−1, a subthreshold swing close to 6 V dec−1, and an impressive on/off ratio of approximately 105. Furthermore, the Ti/In2Te3 Schottky diodes exhibit a low saturation current of 0.4 nA, an ideality factor of 26.7, and a Schottky barrier height of 0.68 eV.